Equal Educational Opportunity: Hearings Before the Select Committee on Equal Educational Opportunity of the United States Senate, Ninety-Second Congress, First Session on Equal Educational Opportunity. Part 16B Inequality in School Finance. - Congress of the U.S., Washington, DC. Senate Select Committee on Equal Educational Opportunity; Congress of the U.S., Washington, DC. Senate Select Committee on Equal Educational Opportunity ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
Testimony recorded in these hearings was presented by David Selden, President, American Federation of Teachers; Dr. Oliver Oldman, Professor of Law and Director of International Tax Programs, Harvard Law School; Allen Manvel, consultant on Government Finance and Statistics, Washington, D.C.; Ralph Nader, Public Interest Research Group, Washington, D.C., accompanied by Jonathan Rowe, attorney; Dr. John E. Coons, professor, School of Law, University of California; Dr. Mark Yudof, Professor, School of Law, University of Texas; and, Mrs. Sarah Carey, Assistant Director, Lawyers Committee for Civil Rights Under Law. (JM)
Availability: Superintendent of Documents, Government Printing Office, Washington, D.C. 20402 ($1.00).
ERIC Note: Hearings held Washington, D.C. Sept 28-30, and Oct 5 1971.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Court Litigation; Educational Finance; Educational Legislation; Educational Needs; Educational Opportunities; Educational Resources; Equal Education; Policy Formation; Property Appraisal; Public Policy; Resource Allocation; School Taxes; Tax Allocation